Chemical equilibration in Pb+Pb collisions at the SPS - Braun-Munzinger, Peter; Heppe, Ingrid; Stachel, Johanna (Arxiv, 1999)
An improved statistical model with excluded volume corrections and resonance decays is introduced and applied to the complete presently available set of particle ratios as measured by the various experiments at the SPS in Pb+Pb collisions. The results imply that a high degree of hadrochemical equilibration is reached at chemical freeze-out in Pb+Pb collisions.